Ragam Bahasa sebagai Unsur Penunjang Harmonisasi Sosial - Putri, Lintang Dewi Fi'liya; Rosyid, Asyhad Abdillah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Indonesia is a multicultural country, proven by the abundance of local wisdom possessed by the Indonesian people. Each tribe and even region has its own variety of languages. Let's just say the Javanese language used every day by the Javanese people. With the assets of languange differences, we can create a bond of harmonization between communities. This is in accordance with the interpretation of the Qur'an in surah al-Hujurat verse 13 that Allah made humans into nations and tribes to know and help each other. There is no difference in degree between one and another. It is on this basis that the Indonesian people must be able to live among existing differences without losing their cultural identity and providing security for the lives of other people's cultures. This research uses qualitative library research and uses an analytical approach to interpreting the Qur’an (tahlili) by collecting related data such as interpretation of the Qur’an and cultural studies. The aim of this research is to invite readers to apply the universal values contained in these holy verses in order to form an inclusive and harmonious society in the global era where diversity is the reality of the times.